Fostering Autonomy in Teaching and Learning English: Focus on Lower Secondary Learners - Urbánková, Kateřina (Univerzita Pardubice, 2025)
This thesis explores the development of learner autonomy in English lessons at the level of the lower secondary school. The theoretical section defines learner autonomy, both generally and within the context of English language education. It further examines the key aspects such as the roles of both teachers and learners, motivation, classroom interaction patterns, and methods supporting autonomous learning. The theoretical part concludes with strategies and techniques that promote autonomy, including self- and peer assessment, learning styles, strategies, and reading techniques - skimming and scanning. In the practical section, the author carries out an empirical study through action research, aiming to increase the autonomy of students in a specific class. After a diagnostic phase, a pedagogical intervention is depicted in the way it was implemented, with a critical evaluation of its outcomes.
Podpora autonomie v hodinách anglického jazyka se zaměřením na žáky druhého stupně
Keywords: learner autonomy; autonomy development; English language teaching; skimming; scanning; action research; autonomie žáka; rozvoj autonomie; výuka anglického jazyka; skimming; scanning; akční výzkum